KEBIJAKAN PEMBERANTASAN TERORISME DALAM TINJAUAN MAQĀṢID AL-SHARĪ'AH - Abdullah Salam A; Maskur Rosyid (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
This article aims to elaborate on the maṣlaḥah and mafsadah sides of the regulations for combating terrorism in Indonesia. Using a normative method with a qualitative approach, this paper finds that the regulations for the delivery of acts of terror have reflected the principle of protecting people's lives. In addition, acts of terror that occurred in Indonesia are more ideologically charged than other factors. This is as a result of the understanding of textual religion. This paper concludes that the policy of eradicating terrorism is one of the best forms of effort to realize the concept of attracting maṣlaḥah and rejecting mafsadah.